Nutritional, Physiochemical, and Biological Value of Muffins Enriched with Edible Insects Flour - Ewelina Zielińska; Urszula Pankiewicz; Monika Sujka (MDPI AG, 2021)
Edible insects are gaining attention as a novel food; however, studies with their use in food are still limited. This study aimed to determine the chemical composition, physical parameters, sensory acceptance, and biological properties of muffins enriched with different levels of cricket (Gryllodes sigillatus) and mealworm (Tenebrio molitor) flours. The approximate composition was analyzed, along with the physical and textural properties, color, and consumer acceptance. Moreover, the antioxidant properties, starch digestibility, and glycemic index were determined in vitro. As we expected, the protein content in muffins supplemented with insect flour increased, while the carbohydrates content decreased. Moreover, the total phenolic content and antioxidant capacity against ABTS·+ and DPPH· increased correspondingly as the percentage of insect flour in the muffins increased. The estimated glycemic index was lower for the fortified muffins than the control (p < 0.05). Additionally, enriched muffins were accepted by consumers, and their taste positively surprised respondents (p < 0.05). Therefore, the results obtained are satisfactory as regards the use of insects for the supplementation of traditional products, and further research into the addition of insects to other nutrient matrices is needed. Furthermore, examining the effect of insect addition on in vivo food biological activity is highly desirable.